HUBUNGAN PARITAS DAN USIA IBU DENGAN KISTA OVARIUM DI RSUD DR. R. GOETENG TARUNADIBRATA PURBALINGGA - Adriani, Prasanti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Ovarian cysts are a tumor, whether small or large, cystic or solid, benign or malignant. RSUD dr. R. Goeteng Tarunadibrata Purbalingga is a referral hospital with the incidence of ovarian cysts the last 2 years has increased significantly in 2015 there was 14% incidence of ovarian cysts and in 2016 there was 39% incidence of ovarian cysts, the case ranks second reproductive disorder. This is likely due to considerable risk factors such as parity and maternal age. The purpose of this study to determine whether there is a relationship between maternal age with the incidence of ovarian cysts in RSUD dr. R. Goeteng Tarunadibrata. Type of research with case control method with retrospective approach. Using total sampling technique counted 60 respondents, sampling group of ovarian cysts 30 respondents and control group 30 respondents miom with consideration because have same characteristic. The research instrument used the master table to record secondary data from the medical record. Result of research of Chi-Square parity with cyst got p value 1,000 for mother age with cyst got p value 0,001. There is relationship of mother age with ovarian cyst in RSUD dr. R. Gorteng Tarunadibrata. Keywords: Parity, Age of Mother, Ovarian Cyst